Constructing Suburbs - Forsyth, Ann (Taylor & Francis, 1999)
Examining the debate between activists and professional planners over the vision of the future of a large growth corridor in Sydney, Australia, this case study maps the history of development from the late sixties to the mid-nineties, during which time serious environmental and financial problems arose. The book outlines five major visions of the future development and examines forms of political, economic, and institutional power applied by the parties in the project, with emphasis on the processes of infrastructure privatization and ecological impacts. The conclusion reflects on contemporary dilemmas about pluralism.